2012
DOI: 10.1186/1471-2415-12-20
|View full text |Cite
|
Sign up to set email alerts
|

High-dose antioxidants for central serous chorioretinopathy; The randomized placebo-controlled study

Abstract: BackgroundTo determine the efficacy of high-dose antioxidants in the acute stage of central serous chorioretinopathy (CSC).MethodsThis was a randomized placebo-controlled study. The patients with acute CSC (onset within 6 weeks) were randomized to receive either high-dose antioxidant tablets (study group A) or placebo tablets (control group B) for 3 months or until the complete resolution of subretinal fluid. After 3 months, additional treatment with laser or photodynamic therapy (PDT) was considered if any fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…We judged 16 of 24 included studies at unclear risk of bias as they had an appropriate method of random sequence generation, but did not clearly describe how the random sequence was assigned or stored, or they did not clearly describe how the random sequence was generated or stored. We judged one included study at high risk of bias as one of the investigators was involved in the sequence generation and assignment (Ratanasukon 2012). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We judged 16 of 24 included studies at unclear risk of bias as they had an appropriate method of random sequence generation, but did not clearly describe how the random sequence was assigned or stored, or they did not clearly describe how the random sequence was generated or stored. We judged one included study at high risk of bias as one of the investigators was involved in the sequence generation and assignment (Ratanasukon 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported that outcome assessors were masked to treatment group and we judged them at low risk of detection bias (Bae 2011; Browning 1993; Chan 2008; Dang 2013; Ratanasukon 2012; Roisman 2013; Sawa 2014; Zhao 2015). Eight studies did not report any masking and the treatments were different and so we judged them at high risk of detection bias (Boscia 2008; Coskun 2014; Kim 2013; Klatt 2011; Leaver 1979; Lim 2010; Rahbani-Nobar 2011; Semeraro 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a study reporting that high-dose antioxidants including lutein for acute CSC 164 produced no benefits in either BCVA or central macular thickness at the end of a 3-month administration period. However, this report showed that antioxidant supplementation decreased the chance for fluorescein leakage and additional treatments [37] . Thus, antioxidant supplementation might contribute to reducing the recurrence and incidence rates of CSC, although its impacts on SRD remission were limited.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, medications such as antioxidants or antiinflammatories might be effective in decreasing the choroidal leakage especially in the early stages of CSC. Ratanasukon et al [28] administrated either high-dose antioxidant tablet or placebo tablets for 3 months or until complete resolution of sub retinal fluid. An additional treatment with laser or PDT was performed if any fluorescein leakage persisted following 3 months.…”
Section: Pradeep Venkatesh Presented a Contradictory Opinion To Whatmentioning
confidence: 99%